PEMERIKSAAN DAN PENGOBATAN MATA DAN KULIT PADA KELOMPOK LANSIA DI NAGARI SUMANIAK - Aisyah Elliyanti; Dian Pertiwi; Arina Widya Murni; Rina Gustia; Hendriati Hendriati; Zelly Dia Rofinda; Yulistini Yulistini; Afriwardi Afriwardi; Elmatris Sy (BULETIN ILMIAH NAGARI MEMBANGUN, 2019)
Health services for the elderly need to get special attention, because they are vulnerable for suffering from disease and tend to experience multi-pathology. Some of the health problems of the elderly in Kenagarian Sumaniak had been identified in community service activities before. Aim: The activity aims is to conduct examination and treatment of eye and skin disorders, as also to conduct counseling on the elderly. Methods: The activity is ayes and skin examination and treatment for elderly people in Kenagarian Sumaniak. Furthermore, counseling was also given regarding physical fitness and maintenance of skin health in the elderly. Results: The event was attended by 70 people aged 52-82 years, 28 men and 52 women. The results of the examination found 64 people suffering from eye disorders with diagnoses were dry eyes 24person, immature cataract 16 person and pterygium14 person. Around 52 people suffering from skin disorders with diagnoses were dermatitis 28 person such as dermatitis allergy, numularis, intertriginosa, sebaroid, and chronic). Conclusions: Health problems in the eyes and skin of the elderly identified are mostly overcome with the medicines provided. Some of them are recommended to go to primary health care to get further health services.